Megacorporation : the infinite times of Alphabet - Whelan, Glen (Cambridge : Cambridge University Press, 2021)
When the scale and scope of influence that a corporation wields is so great that it eclipses that of nearly all other corporations combined, it attains megacorporate status. Whelan proposes that, amongst the current big tech cohort, it is only Alphabet, the parent company of Google, that can be categorized as such. In advancing a novel philosophical perspective, and aspiring to an amoral ideal of analysis, Whelan reveals Alphabet's activities to be informed by the ideology of infinite times, consequently transforming how we experience the past, present and the future at personal and social levels. By shining a light on such corporate existential impacts, Megacorporation: The Infinite Times of Alphabet opens up a new field of research that makes the philosophical analysis of business and society an everyday concern. This novel study on corporate social influence will appeal to readers interested in big tech, business and society, political economy and organization studies.
Title from publisher's bibliographic system (viewed on 09 Apr 2021).
Keywords: Alphabet Inc; Internet industry -- United States; Social responsibility of business -- United States; Big business -- Social aspects -- United States; Conglomerate corporations -- United States